Hydrogen Evolution Reaction: Engineered 2D Transition Metal Dichalcogenides—A Vision of Viable Hydrogen Evolution Reaction Catalysis (Adv. Energy Mater. 16/2020). Issue 16 (28th April 2020) - Lin, Liangxu; Sherrell, Peter; Liu, Yuqing; Lei, Wen; Zhang, Shaowei; Zhang, Haijun; Wallace, Gordon G.; Chen, Jun
Abstract : In article number 1903870, Liangxu Lin, Jun Chen and co‐workers report the research progress, discuss future directions and emerging trends of 2D transition metal dichalcogenides in the electrochemical hydrogen evolution reaction, providing a pathway forward for viable hydrogen evolution.